Impact of within-visit systolic blood pressure change patterns on blood pressure classification: the Cardiovascular Risk in Young Finns Study - Meng Yaxing; Magnussen Costan G.; Wu Feitong; Juonala Markus; Buscot Marie-Jeanne; Pahkala Katja; Hutri-Kähönen Nina; Kähönen Mika; Laitinen Tomi; Viikari Jorma S. A.; Raitakari Olli T.; Sharman James E. (OXFORD UNIV PRESS, 2022)
Aims Most international guidelines recommend that repeat blood pressure (BP) readings are required for BP classification. Two international guidelines diverge from this by recommending that no further BP measurements are required if the first clinic BP is below a hypertension threshold. The extent to which within-visit BP variability patterns change over time, and whether this could impact BP classification is unknown. We sought to examine this.
Methods and results Data were from the Cardiovascular Risk in Young Finns Study, a prospective cohort study. Up to 2799 participants were followed from childhood (9-15 years) to adulthood (18-49 years) over up to six visits. Patterns of within-visit systolic BP (SBP) variability were defined as no-change, decrease, increase between consecutive readings (with 5 mmHg change thresholds). Classification of SBP (normal, high-normal, hypertension) using the first reading was compared with repeat readings. On average, SBP decreased with subsequent measures, but with major individual variability (no-change: 56.9-62.7%; decrease: 24.1-31.6%; increase: 11.5-16.8%). Patterns of SBP variability were broadly similar from childhood to adulthood, with the highest prevalence of an increase among participants categorized with normal SBP (12.6-20.3%). The highest prevalence of SBP reclassification occurred among participants with hypertension (28.9-45.3% reclassified as normal or high-normal). The prevalence of reclassification increased with the magnitude of change between readings.
Conclusion There is a major individual variation of within-visit SBP change in childhood and adulthood and can influence BP classification. This highlights the importance of consistency among guidelines recommending that repeat BP measurements are needed for BP classification.